Improving Students’ Skills in Translation through Students-Teams Achievement Division (STAD) Technique - Syarwan Ahmad (AT-TA'LIM, 2015)
This classroom action rresearch was aimed at improving students’ skills in translating at the English Department of the State Islamic University (UIN) Ar-Rarniry Banda Aceh by using the Student-Teams Achievement Division (STAD) Technique. Throughout the entire cycles, students worked in groups of 4-5 persons to plan and write their translations. The study showed that the average score of pre- test (66) increased dramatically to reach 86, and moved up a little higher (87) after the second cycle. It is recommended that STAD Cooperative Technique be implemented in teaching translation courses.  Key words: Teaching translation; STAD; UIN Aceh.Copyright © 2015 by Al-Ta'lim All right reserved